Comparative analysis of aging policy reforms in Argentina, Chile, Costa Rica, and Mexico. Issue 3 (27th May 2019) - Calvo, Esteban; Berho, Maureen; Roqué, Mónica; Amaro, Juan Sebastián; Morales-Martinez, Fernando; Rivera-Meza, Emiliana; Gutiérrez Robledo, Luis Miguel F.; López, Elizabeth Caro; Canals, Bernardita; Kornfeld, Rosa
ABSTRACT: This investigation uses case studies and comparative analysis to review and analyze aging policy in Argentina, Chile, Costa Rica, and Mexico and uncovers similarities and relevant trends in the substance of historical and current aging policy across countries. Initial charity-based approaches to poverty and illness have been gradually replaced by a rights-based approach considering broader notions of well-being, and recent reforms emphasize the need for national, intersectoral, evidence-based policy. The results of this study have implications for understanding aging policy in Latin America from a welfare regime and policy makers' perspective, identifying priorities for intervention and informing policy reforms in developing countries worldwide.